The RNA chaperone Hfq has a multifaceted role in Edwardsiella ictaluri - Akgul, Ali; Kalindamar, Safak; Kordon, Adef O.; Abdelhamed, Hossam; Ibrahim, Iman; Tekedar, Hasan C.; Karsi, Attila (Frontiers in Cellular and Infection Microbiology, 2024)
Edwardsiella ictaluri is a Gram-negative, facultative intracellular bacterium that causes enteric septicemia in catfish (ESC). The RNA chaperone Hfq (host factor for phage Qβ replication) facilitates gene regulation via small RNAs (sRNAs) in various pathogenic bacteria. Despite its significance in other bacterial species, the role of hfq in E. ictaluri remains unexplored. This study aimed to elucidate the role of hfq in E. ictaluri by creating an hfq mutant (EiΔhfq) through in-frame gene deletion and characterization. Our findings revealed that the Hfq protein is highly conserved within the genus Edwardsiella. The deletion of hfq resulted in a significantly reduced growth rate during the late exponential phase. Additionally, EiΔhfq displayed a diminished capacity for biofilm formation and exhibited increased motility. Under acidic and oxidative stress conditions, EiΔhfq demonstrated impaired growth, and we observed elevated hfq expression when subjected to in vitro and in vivo stress conditions. EiΔhfq exhibited reduced survival within catfish peritoneal macrophages, although it had no discernible effect on the adherence and invasion of epithelial cells. The infection model revealed that hfq is needed for bacterial persistence in catfish, and its absence caused significant virulence attenuation in catfish. Finally, the EiΔhfq vaccination completely protected catfish against subsequent EiWT infection. In summary, these results underscore the pivotal role of hfq in E. ictaluri, affecting its growth, motility, biofilm formation, stress response, and virulence in macrophages and within catfish host.